Panorama da produç\~ao acadêmica sobre alimentaç\~ao escolar e agricultura familiar no Brasil - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– This study aimed to analyze the scientific production on the relationship between state (public policies), school feeding and family agriculture in Brazil, before and after Law n. 11,947/2009, which reformulated the regulatory framework of the National School Feeding Program (PNAE). The objective was to verify how these terms have been addressed in the literature, investigating the diversity of possible problems and interpretations that the interface between them raises. The methodological path chosen is divided into two parts. First, a bibliometric survey was carried out in order to draw a quantitative overview of the production of interest, whose selected researches are presented regarding their publication periods, areas of knowledge, dissemination channels, methodological approaches and keywords most used. Subsequently, a thematic categorization of all selected works was performed, aiming at identifying the main emphasized subjects, to then highlight the general evidences found and systematized from a qualitative review of its bibliographic content. Thus, a privileged approach was obtained about the operational reality of the PNAE, since the analyses demonstrate concrete aspects about the challenges and potentials associated with the insertion of family agriculture in institutional markets, while emphasizing possible factors for the potentiation of this instrument in the Brazilian territory.
Keywords: H83; J23; 330; school feeding; family agriculture; public procurement; food and nutritional security PNAE